Use of high-dose matrix formulation of vitamin D for the prevention and treatment of vitamin D deficiency, including in comorbid patients - Board Editorial (Терапевтический архив)
On May 22, 2024, an Interdisciplinary Expert Council, "A new chapter in the treatment of vitamin D deficiency and insufficiency: 50,000 IU in one matrix tablet – discovering the potential together", was held in Moscow, dedicated to the advantages and features of the innovative high-dose vitamin D recently launched on the Russian market (Devilam 5000 and 50,000 IU in one matrix tablet), with the participation of leading experts of various medical specialties. During the Council, new opportunities for the use of high-dose vitamin D in comorbid patients in need of rapid and effective correction of preexisting vitamin D deficiency or insufficiency were discussed.